Factors affecting self‐care among community‐dwelling hypertensive older adults: A cross‐sectional study - Soo Youn Jung; Kyoung Ja Moon (Wiley, 2023)
Abstract Aim To examine self‐care behaviours among older adults with hypertension and identify related factors, including cognitive function, religious belief and comorbidities. Design A cross‐sectional study. Methods Self‐care behaviours included diet and health. Participants completed a survey including items on demographics, disease‐related characteristics and self‐care behaviours and underwent cognitive function tests. Data were analysed using descriptive statistics, and multiple regression analysis was performed to analyse the factors affecting self‐care. Results Regarding diet behaviour, older religious adults and those with higher scores on the Montreal Cognitive Assessment‐Korean version had higher levels of self‐care scores according to the HBP‐SC. Regarding health behaviour, older adults with no comorbidities had higher levels of self‐care scores according to the HBP‐SC. Conclusion Factors affecting self‐care diet behaviour include religion and Montreal Cognitive Assessment‐Korean version scores and those affecting health behaviour include comorbidities among older adults with hypertension. Therefore, to improve their self‐care behaviours, their religious practices and comorbidities should be considered, cognitive function should be assessed, and tailored education should be provided. Implications for the Profession and/or Patient Care This study investigated factors affecting self‐care behaviours of hypertensive older adults in South Korea. The self‐care was divided into diet and health behaviours. The factors influencing diet behaviour were religion and Montreal Cognitive Assessment‐Korean version scores, and the factor influencing health behaviour was comorbidities. We also investigated self‐care behaviour patterns. Older adults with hypertension were good at controlling alcohol consumption and did not forget to fill prescriptions. However, they were poor at reading nutrition labels to check on sodium content and checking blood pressure at home. Therefore, nurses could develop interventions considering these influencing factors and behavioural patterns to improve self‐care behaviours and enhance health for older adults with hypertension. Impact Hypertension in older adults affects their health conditions and performance of self‐care behaviours. Nurses could assess self‐care based on diet and health behaviours. Additionally, further developing tailored programmes is recommended considering factors like religious belief, cognitive function and comorbidities. Reporting Method This study followed the STROBE guidelines. Patient or Public Contribution This study used a convenience sample of 105 participants aged ≥ 65 years recruited from a Korean hospital.